Updating the Distribution and Conservation Status of the Endemic Nabatean Thyme (Thymbra nabateorum) - Abdulkarem, Ayman; Elgharib, Ahmed; Darwish, Mohammed; Assaeed, Abdulaziz; Alenezi, Ali; Van Essen, Lourens; Soultan, Alaaeldin (Conservation, 2025)
Nabatean thyme (Thymbra nabateorum (Danin & Hedge) Bräuchler) is a perennial herb species under the Lamiaceae family, first described in 1998. The species is thought to be endemic to Jordan with only six known records. However, recent fieldwork has uncovered new patches of Nabatean thyme in northwestern Saudi Arabia. This study aimed to determine the global conservation status and update the distribution of Nabatean thyme. To achieve this, we conducted extensive fieldwork and used the collected occurrences to calculate species Extent of Occurrence (EOO) and Area of Occupancy (AOO). We recorded Nabatean thyme in sandstone grooves within open plains at altitudes of 850 to 1350 m, with its largest population occurring outside its historical range, rendering it endemic to northwest Arabia. The primary threats to Nabatean thyme across its range include overgrazing, excessive harvesting for medicinal purposes, and habitat fragmentation. Nabatean thyme has an EOO of 47,585 km² and an AOO of 136 km². Accordingly, we recommend considering Nabatean thyme as an Endangered species under the B2ab(iii) and C2a(ii) IUCN criteria. We recommend integrating both in situ and ex situ conservation programs to improve the conservation status and ensure the sustainability of Nabatean thyme.